Sejarah Perbandingan Sistem Pendaftaran Paten Di Amerika Serikat Dengan Di Indonesia - Elisa Sugito; Erwin Syahruddin (Batulis Civil Law Review, 2021)
Patent protection in a country cannot be separated from the registration system adopted in that country. In the United States the patent registration system is based on the first-to-invent principle. Even though the United States uses the first-to-invent principle, the United States also regulates protection requirements as European countries, Japan and Indonesia are in the form of new discoveries, containing inventive steps, and can be applied in industry. Meanwhile in Indonesia, the patent protection system used is the first to file system, which is a system that grants patent rights to those who first register a new invention in accordance with the requirements. The purpose of this research is to study and analyze the comparative history of the patent registration system in the United States with the patent registration system in Indonesia. The type of research method used is normative legal research with a comparative law approach and a legal history approach. The results of the study found that patent protection in European countries, the United States, Japan and Indonesia has similarities in protection requirements that regulate novelty, inventive steps, and industrial applications.